Affective filter influence on students' initiating the b.a. english major at the Universidad Nacional, Chorotega branch in Nicoya, Guanacaste, Costa Rica - Dover, Yendry (2011)
Affective filter is a commoly accepted component in foreign language learning for adults, are internalized emotional barriers frequently established by learners as a way of psychologically protecting them when confronting the challenge of producing the target language Krashen (1987). With this natural defense mechanism is attempting to help the individuals from damaging their egos, it is in fact counter-productive to the language learning process. This qualitative study explores and describes the negative impact of affective filters in a group of entrance level, young adult students at the Universidad Nacional, Chorotega Branch campus in Guanacaste, Costa Rica. In addition, it tests some strategies in lowering the affective filter in this particular group. The results showed that there was a significant impact in how affective filter delimit the learning process and the need for professionals in the field of language learning to address this issue especially in the beginning of the language acquisition process.